'The' market for higher education: Does it really exist? - William E. Becker; David K. Round (Institute for the Study of Labor (IZA), 2009)
Higher education, like any other commodity or service, has been viewed in a variety of economic frameworks. Little of this work, however, appears to have made any effort to define carefully the boundaries of the relevant market for higher education, which is the subject of this particular inquiry. Market definition is an essential preliminary step before any academic or policy investigation can properly be made into the forces that determine the behavior of the buyers and sellers of higher education, those who provide inputs into the education process, or those who fund or otherwise subsidize it. The authors spell out the key economic dimensions of a market, and illustrate their relevance for research that seeks to analyze the players and policies in the many distinct domestic and international markets that exist for the inputs and outputs of the higher education sector.
urn:nbn:de:101:1-2009041455
Keywords: A1; I2; L3; 330; Competition; efficiencies; market boundaries; markets; higher education; public policy; Hochschule; Relevanter Markt; Bildungsökonomik; Theorie; Welt